KETAHANAN PANGAN MELALUI BUDIDAYA JANGKRIK DI ERA SOCIETY 5.0 - Putra, Purnama; Diyono, Wahid; Khoiriyah, Ummi; Nurhidayah, Siti; Putrianika, Puput; Widyowati, Dian Desty (DEVOSI, 2025)
This community service activity was motivated by the low utilization of cricket farming potential as an alternative creative economic enterprise and a source of highly nutritious, environmentally friendly food. The implementation method was carried out through observation, planning, purchasing cricket eggs, cultivation training, and mentoring for participants consisting of lecturers and students from Universitas Islam 45, Bekasi City, with a total of 335 participants, 150 of whom participated offline and 185 participated online through a video conferencing application. The results of the activity showed that participants gained an in-depth understanding of cricket farming techniques, from hatching eggs to harvesting, the importance of using fresh feed, the nutritional value contained in crickets, and the economic potential that can be developed into high-value products. The obstacles that arose in the form of limited initial experience in farming were overcome through a hands-on approach and interactive discussions. In the context of the Society 5.0 era, this activity also integrated digital technology with cricket farming through microcontrollers and humidity sensors. The conclusion of this activity is that cricket farming has proven to be an alternative for strengthening food security, developing productive businesses, and increasing applicable academic knowledge in supporting sustainable economic development at the local level.